Integrating multiple omics and machine learning to reveal the prognostic value of endoplasmic reticulum stress gene FKBP10 in gastric cancer - Chen, Xuanyu; Liu, Chenchen; Wang, Yuqin; Yu, Aoyang; Pei, Zichen; Yao, Zhiyuan; Li, Gengchen; Yan, Lin; Zhang, Xitai; Han, Zhengxiang (Translational Cancer Research, 2026)
Stomach adenocarcinoma (STAD) remains a leading cause of cancer-related mortality worldwide, with limited prognostic biomarkers and heterogeneous responses to immunotherapy. Endoplasmic reticulum stress (ERS) plays a critical role in tumor progression and immune modulation, yet its comprehensive prognostic value in STAD has not been systematically characterized. This study aims to identify ERS-related genes with prognostic significance and elucidate their role in the tumor microenvironment.